2016
DOI: 10.1007/s40279-016-0564-3
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Dysmorphia Symptomatology and Associated Psychological Features in Bodybuilders and Non-Bodybuilder Resistance Trainers: A Systematic Review and Meta-Analysis

Abstract: MD symptomatology was greater in BBs than in NBBRTs. Anxiety and social physique anxiety, depression, neuroticism, and perfectionism were positively associated with MD, while self-concept and self-esteem were negatively associated. It remains unclear whether these characteristics are exacerbated by bodybuilding, or whether individuals with these characteristics are attracted to the bodybuilding context.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
121
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 109 publications
(136 citation statements)
references
References 70 publications
9
121
0
6
Order By: Relevance
“…Additionally, the logistic regression results showed that muscle dysmorphia can predict the likelihood of use of supplements and drugs by bodybuilders. These findings are in line with results of Babusa and Tury [14], Olivardia et al [24], and Cella et al [11]. Literature shows the relationship between muscle dysmorphia and high levels of anxiety [25], depression [16], and low self-esteem [14].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Additionally, the logistic regression results showed that muscle dysmorphia can predict the likelihood of use of supplements and drugs by bodybuilders. These findings are in line with results of Babusa and Tury [14], Olivardia et al [24], and Cella et al [11]. Literature shows the relationship between muscle dysmorphia and high levels of anxiety [25], depression [16], and low self-esteem [14].…”
Section: Discussionsupporting
confidence: 90%
“…Michelle et al in a study, showed that bodybuilders have symptoms of muscle dysmorphia more than other resistance athletes; generally, bodybuilders are at a greater risk than non-bodybuilders and non-athletic ordinary people for the symptoms of muscle dysmorphia [11,15].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This cult of the body affects many male athletes or nonathletes who choose to practice bodybuilding to achieve the thin and muscular body ideal (e.g., Mitchell et al 2017). Influenced by this male body ideal, men develop certain deviations in their behavior (e.g., Mitchell et al 2017).…”
Section: Introductionmentioning
confidence: 99%